Determinación de las causas de búsquedas sin resultados en un catálogo bibliográfico en línea mediante el análisis de bitácoras de transacciones : el caso de la Pontificia Universidad Católica del Perú - Sifuentes Arroyo, Raúl Alejandro (2013)
The present investigation is aimed at determining the causes of searches with zero results in the OPAC of the Sistema de Bibliotecas Pontificia Universidad Catolica del Peru during 2012 year. For this purpose, a log transaction analysis of the OPAC´s searches was done as a methodology. Three causes of searches with zero result were found: 1) Terms mismatched: words or phrases written correctly in search statements which do not match those used in the bibliographic description and subject terminology assigned to each bibliographic record. 2) Wrong writing in search statements due to typographical and spelling mistakes. 3) Wrong index selection: when a user selects a wrong index for his/her search statement. A more detailed analysis was done for each OPAC's index. Suggestions are offered regarding to reinforcement in OPAC searches training, improve search engine interface, and use of log transactions analisys of OPAC´s searches as a methodology to detect library materials demand not in its physical and virtual collections.